A Non-purine Xanthine Oxidoreductase Inhibitor Reduces Albuminuria in Patients with DKD: A Randomized Controlled Trial. Issue 8 (26th August 2021) - Bakris, George L.; Mikami, Hidetaka; Hirata, Masayuki; Nakajima, Akihiro; Cressman, Michael D.
Visual Abstract: Abstract: Key Points: Whether xanthine oxidoreductase inhibitors (XORIs) can be renoprotective for type 2 diabetic kidney disease (T2DKD) is unclear. In this randomized trial, a novel XORI, TMX-049 200 mg, reduced albuminuria by 35% in patients with T2DKD, without any relevant safety concerns. Aside from lowering uric acid levels, xanthine oxidoreductase inhibition in the kidney may play a key role for the management of T2DKD. Background: Diabetic kidney disease (DKD) is characterized by albuminuria and reduced renal function. Whether xanthine oxidoreductase inhibitors (XORIs) have a renoprotective effect in DKD patients with type 2 diabetes remains controversial. We conducted a proof-of-concept study to investigate the renal effects of a novel XORI, TMX-049, in patients with DKD and type 2 diabetes. Methods: This is a multicenter, 12-week, randomized, double-blind, placebo-controlled phase 2a trial conducted at 49 centers across the United States between April 2018 and June 2019. In total, 130 patients with type 2 diabetes, urine albumin-creatinine ratio (UACR) 200 − 3000 mg/g, eGFR ≥30 ml/min per 1.73 m 2, and serum uric acid (sUA) 4 − 10 mg/dl were randomized 1:1:1 to TMX-049 200 mg ( n =44) or 40 mg ( n =44), or placebo ( n =42). The primary end point was change in log-transformed UACR at week 12 from baseline. The secondary end points included changes in UACR, eGFR, and sUA from baseline. Results: The least squares mean differences for changes in log-transformed UACR from baseline to week 12 compared with placebo were −0.43 (95% confidence interval [95% CI], −0.82 to −0.04, P =0.03) for TMX-049 200 mg and −0.05 (95% CI, −0.44 to 0.34, P =0.80) for 40 mg; a 35% reduction in UACR was observed with TMX-049 200 mg (ratio versus placebo, 0.65; 95% CI, 0.44 to 0.96) but not 40 mg (0.95; 95% CI, 0.64 to 1.41). Throughout the treatment period, marked reductions in sUA levels but no changes in eGFR were observed with both TMX-049 doses. TMX-049 was generally well tolerated, although two patients with TMX-049 200 mg developed gout. Conclusions: TMX-049 200 mg reduced albuminuria at 12 weeks in patients with DKD and type 2 diabetes. TMX-049 may exert a renoprotective effect independent of its sUA-lowering effect.